Exploring the dynamics of adult Axin2 cell lineage integration into dentate gyrus granule neurons - Sharifi, Khadijeh A.; Farzad, Faraz; Soldozy, Sauson; DeWitt, Matthew R.; Price, Richard J.; Sheehan, Jason; Kalani, M. Yashar S.; Tvrdik, Petr (Frontiers in Neuroscience, 2024)
The Wnt pathway plays critical roles in neurogenesis. The expression of Axin2 is induced by Wnt/β-catenin signaling, making this gene a sensitive indicator of canonical Wnt activity. We employed pulse-chase genetic lineage tracing with the Axin2-CreERT2 allele to follow the fate of Axin2+ lineage in the adult hippocampal formation. We found Axin2 expressed in astrocytes, neurons and endothelial cells, as well as in the choroid plexus epithelia. Simultaneously with tamoxifen induction of Axin2 fate mapping, the dividing cells were marked with 5-ethynyl-2´deoxyuridine (EdU). Tamoxifen induction resulted in significant increase of dentate gyrus granule cells three months later; however, none of these neurons contained EdU signal. Conversely, six months after the tamoxifen/EdU pulse-chase labeling, EdU-positive granule neurons were identified in each animal. Our data imply that Axin2 is expressed at several different stages of adult granule neuron differentiation and suggest that the process of integration of the adult-born neurons from certain cell lineages may take longer than previously thought.